Doryforos w pancerzu – czyli o wizerunku Augusta z Prima Porta słów kilka - Kwaśny, Mariusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
Images of emperors of Julio-Claudian dynasty and especially the most famous representation of Octavian Augustus of Prima Porta, became the prototype representation of emperors-officers for the representatives of the next dynasty wielding Roman Empire. Statue of Augustus, no doubt modeled on Doryphoros – a statue made by Polykleitos (sculptor-foundry of classical Greek era) is an example of the propaganda image of the emperor. Statua loricata – a statue of Octavian in the breastplate – presents emperor during adlocutio – speech addressed to the army. Models of classical Greek sculpture exhibit at the statue of the emperor by using position called contrapposto and deification of the emperor by showing him barefoot. Among other things, lack of shoes indicates that the statue of Octavian was made after the death of the ruler. The divine pedigree of the emperor was also marked by the attributes that are on his right leg – Cupid and dolphin. Head of Augustus was also performed on the model Doryphoros, and its distinctive hairstyle is defined as a „Primaporta” type. The most important element of the Prima Porta statue of the emperor is his breastplate. Armor classified as a torso cuirass is here as long type – with the downward extension, meant to protect the lower abdominal part. Armor probably originally made of leather, on the statue of Octavian is very richly decorated with historical and mythological reliefs. In the central part of the armor was shown a scene that shows the Parthians transferring military signs (signum militare) that have been lost by Marcus Crassus in 53 BC. On both sides of middle scene, were placed two women – personifications of lands conquered by Rome. The whole presentation is observed by the images of deities: Tellus Mater – Mother of Earth, Apollo, Diana, the god of the Sun – Sol, goddess of the moon – Luna and the God of heaven – Caelus. Statue of Augustus from Prima Porta combines classical designs of sculptures of Polykleitos period and contemporary elements of the propaganda of the imperial policy of the Augustus principate. Sculpture showing the first emperor of the Roman Empire, dressed in breastplate has become an example image of the rulers shown as the leaders of the army but also showing the immense power of propaganda policy.